2015
DOI: 10.4236/ojtr.2015.34018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Free Water Protocol on Inpatients in a Neuro-Rehabilitation Setting

Abstract: Background: Dysphagia is common among stroke and acquired brain injury (ABI) patients and may result in aspiration. To reduce the risk of thin liquid aspiration, patients are often restricted to thickened fluids. There is considerable clinical interest in the risks and benefits of offering oral water intake, in the form of water protocols, to patients with thin-liquid dysphagia. Objectives: A controlled pilot study of a free water protocol was undertaken at Riverview Health Centre, in Winnipeg, Manitoba to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 20 publications
(26 reference statements)
4
18
0
4
Order By: Relevance
“…We performed a meta-analysis of the six RCTs 13,20–24 that examined the incidence of pneumonia in thin water protocols vs. thickened liquids (Figure 2, available online). Data from 135 patients were extracted from the six studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We performed a meta-analysis of the six RCTs 13,20–24 that examined the incidence of pneumonia in thin water protocols vs. thickened liquids (Figure 2, available online). Data from 135 patients were extracted from the six studies.…”
Section: Resultsmentioning
confidence: 99%
“…All seven studies were written in English. Five studies were published in full text; 13,14,[20][21][22] two were published in conference handouts. 23,24 One of the seven studies was a large, multicenter RCT, which compared the efficacy of postural adjustment and fluid modification in preventing dysphagia-related adverse events.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is consistent with previous research on the FWP in the rehabilitation setting. 1,[20][21][22][23][24][25] Participants in the experimental group showed a trend toward decreased days to discharge from the study, but the small number of participants that were followed precluded statistical testing.…”
Section: Discussionmentioning
confidence: 99%
“…19 To date, 7 studies of the FWP in the rehabilitation setting have been published. 1,[20][21][22][23][24][25] Of these, 6 did not reveal elevated rates of aspiration pneumonia in participants on free water protocols. One study, however, showed lung complications, including aspiration pneumonia, in 6 of 42 participants (14%) randomized to a group with access to water but no lung changes in the control group (n = 34).…”
mentioning
confidence: 99%